How does future tourism affect today's depletion of natural resources in a globalized world? - Michael Hübler (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2014)
This paper sets up a two-period, two-sector trade model of a developing country which is abundant in a natural resource but scarce in industrial goods. It shows that lower future travel costs, rising demand for tourism and higher preferences for the environment slow down today's depletion of the non-renewable natural resource that can be used for consumption or for exporting tourism services. The benefits that accrue from sustainable resource use can be distributed over time such that the myopic developing country and forward-looking industrialized countries, which demand tourism services, are better off.
Keywords: F18; H23; O13; 330; international trade; tourism; non-renewable resource